2019
DOI: 10.24016/2019.v5n2.167
|View full text |Cite
|
Sign up to set email alerts
|

Estructura factorial del Cuestionario de Fusión Cognitiva en universitarios de Lima

Abstract: Background: Cogni ve fusion is a core concept in Acceptance and Commitment Therapy. The Cogni ve Fusion Ques onnaire (CFQ) was developed as a unidimensional measure that would overcome the limita ons of previous endeavors. Method: The current study analyzed the factor structure of the CFQ in Peruvian undergraduates (n = 450, 53% female). It also examined whether such structure was invariant between males and females. Results: Data supported the hypothesized unidimensionality, as well as strict invariance. No d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 36 publications
4
8
1
1
Order By: Relevance
“…In the present study, the Spanish translation of the CFQ was used (Romero-Moreno, Márquez-González, Losada, Gillanders, & Fernández-Fernández, 2014), as modified by Ruiz, Suárez-Falcón, Riaño-Hernández, and Gillanders (2017). This version of the CFQ has been previously tested in Peruvian undergraduates, thereby confirming its unidimensional structure and high reliability (Valencia & Falcón, 2019). Reliability was very high in our data (ω = .92).…”
Section: Cognitive Fusion Questionnaire (Cfq; Gillanders Et Al 2014) Cognitive Fusion Was Measuredsupporting
confidence: 68%
“…In the present study, the Spanish translation of the CFQ was used (Romero-Moreno, Márquez-González, Losada, Gillanders, & Fernández-Fernández, 2014), as modified by Ruiz, Suárez-Falcón, Riaño-Hernández, and Gillanders (2017). This version of the CFQ has been previously tested in Peruvian undergraduates, thereby confirming its unidimensional structure and high reliability (Valencia & Falcón, 2019). Reliability was very high in our data (ω = .92).…”
Section: Cognitive Fusion Questionnaire (Cfq; Gillanders Et Al 2014) Cognitive Fusion Was Measuredsupporting
confidence: 68%
“…Regarding the prevalence of CF, the sample had a total mean close to half of the total score of the instrument. In this case, the presence of CF is relatively moderate, which differs from other studies among college students that suggest low levels of CF (Flynn et al, 2018;Ruiz et al, 2017;Valencia & Falcón, 2019). This suggests a different dynamic of the phenomenon within the Ecuadorian context that will require further studies.…”
Section: Discussioncontrasting
confidence: 75%
“…Likewise, a study on Colombian college students (with slight linguistic modifications) concluded the unidimensionality of the measure and its excellent internal consistency (α = .89; Ruiz et al, 2017). In the Peruvian population, it obtained a similar dimensionality and internal consistency (ω = .916; Valencia & Falcón, 2019); and in the Brazilian population (correlating the errors of items 1 and 2, and 2 and 3) it got an adequate internal consistency (α = .93;Lucena-Santos et al, 2017). As it relates to Ecuador, the psychometric properties of the CFQ are unknown in any population segment.…”
Section: Cognitive Fusion Assessmentmentioning
confidence: 90%
“…There are no reversed items, so that all of them are averaged in order to get a total score. An existing Spanish version (Ruiz et al, 2017), which had been previously tested in Peruvian undergraduates (Valencia & Falcón, 2019), was used in this study. Reliability was high in the present data (ω = .922).…”
Section: Methodsmentioning
confidence: 99%